Curvilinear squeeze film bearing with porous wall lubricated by a Rabinowitsch fluid - Walicka, Anna; Walicki, Edward; Jurczak, Paweł; Falicki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The present theoretical analysis is to investigate the effect of non-Newtonian lubricant modelled by a Rabinowitsch fluid on the performance of a curvilinear squeeze film bearing with one porous wall. The equations of motion of a Rabinowitsch fluid are used to derive the Reynolds equation. After general considerations on the flow in a bearing clearance and in a porous layer using the Morgan-Cameron approximation the modified Reynolds equation is obtained. The analytical solution of this equation for the case of a squeeze film bearing is presented. As a result one obtains the formulae expressing pressure distribution and load-carrying capacity. Thrust radial bearing and spherical bearing with a squeeze film are considered as numerical examples.
Keywords: non-Newtonian fluid; Rabinowitsch model; curvilinear squeeze film bearing; porous layer